2017
DOI: 10.12691/env-5-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Local Community Participation in Restoration of Watersheds in Uganda

Abstract: Despite the involvement of the local community in Awoja watershed activities, restoration was not fully achieved. Studies on community participation in Awoja watershed have focused on its importance with little known on the extent to which they participate, yet the level of community participation determines the success of restoration of watersheds. This study analysed the extent of local community participation in restoration of Awoja watershed of Eastern Uganda. It was conducted in Ngora district and respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…From the key informant interviews however it was revealed that resource user groups navigated through these power centers to circumvent the rules that they felt were not in their favor. While participation in watershed restoration is important [20], the findings from this study show that participation in watershed management can be used by community leaders to renegotiate the environmental rules. Therefore, whereas participation brought about involvement of communities in watershed management, the communities used this opportunity to navigate through the power centers and circumvent the environmental rules and regulations.…”
Section: Discussionmentioning
confidence: 84%
“…From the key informant interviews however it was revealed that resource user groups navigated through these power centers to circumvent the rules that they felt were not in their favor. While participation in watershed restoration is important [20], the findings from this study show that participation in watershed management can be used by community leaders to renegotiate the environmental rules. Therefore, whereas participation brought about involvement of communities in watershed management, the communities used this opportunity to navigate through the power centers and circumvent the environmental rules and regulations.…”
Section: Discussionmentioning
confidence: 84%